FOSTERING RESILIENCE IN STUDENTS: COPING WITH ADVERSITY IN EDUCATION (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
This article discusses the concept of resilience and its importance in the context of education. It identifies various factors that may undermine student resilience, such as poverty, trauma, family instability, and academic stress, and highlights protective factors that promote the development of student resilience, such as supportive relationships, positive school climates, and access to resources and opportunities for growth and success. The article also presents evidence-based strategies for fostering resilience, such as social and emotional learning, positive youth development, and school connectedness, and emphasizes the role of teacher and staff support and community partnerships and resources in building student resilience.